Endoscopic Endonasal Transclival Odontoidectomy for Basilar Invagination: Operative Video and Technical Nuances - Liu, James K.; Dodson, Vincent N.; Zhao, Kevin; Eloy, Jean Anderson (Journal of Neurological Surgery Part B: Skull Base, 2020)
Basilar invagination is a congenital or acquired craniovertebral junction abnormality where the tip of the odontoid process projects through the foramen magnum which can cause severe symptomatic compression of the brainstem and spinal cord. If left untreated, patients can develop progressive quadriparesis. Traditionally, basilar invagination can be treated with cervical traction and posterior stabilization. However, in irreducible cases, anterior decompression via a transoral or endonasal approach may be necessary. In this operative video, we demonstrate an endoscopic endonasal transclival approach for odontoidectomy to successfully treat a 37-year-old female with severe basilar invagination causing symptomatic compression on the cervicomedullary junction resulting in unsteady gait and motor weakness. The patient had Klippel–Feil syndrome where the C1 arch was assimilated to the foramen magnum and transclival drilling was needed to adequately access the odontoid process for removal. A second-stage posterior occipitocervical stabilization and fusion was performed the following day. Immediate postoperative imaging showed excellent decompression of the cervicomedullary junction. Postoperatively, the patient had significant improvement in gait and motor strength in all extremities, and was ambulating independently without assistance at 1 year after surgery. The endoscopic endonasal transclival odontoidectomy is a useful strategy to treat severe irreducible basilar invagination causing symptomatic neural compression. The surgical technique and nuances are described in a step-by-step fashion in this illustrative operative video.The link to the video can be found at: https://youtu.be/HL4K7KqJEJM.
Keywords: endoscopic endonasal approach; transclival odontoidectomy; endoscopic skull base surgery; basilar invagination; craniovertebral junction; operative video